5x-4x+3=x

Simple and best practice solution for 5x-4x+3=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-4x+3=x equation:


Simplifying
5x + -4x + 3 = x

Reorder the terms:
3 + 5x + -4x = x

Combine like terms: 5x + -4x = 1x
3 + 1x = x

Solving
3 + 1x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
3 + 1x + -1x = x + -1x

Combine like terms: 1x + -1x = 0
3 + 0 = x + -1x
3 = x + -1x

Combine like terms: x + -1x = 0
3 = 0

Add '-3' to each side of the equation.
3 + -3 = 0 + -3

Combine like terms: 3 + -3 = 0
0 = 0 + -3

Combine like terms: 0 + -3 = -3
0 = -3

Simplifying
0 = -3

Combine like terms: 0 + 3 = 3
3 = -3 + 3

Combine like terms: -3 + 3 = 0
3 = 0

The solution to this equation could not be determined.

See similar equations:

| 747-60x=300 | | 5(z+2)=25 | | 7-3x=y | | 2345x-23167=3 | | 747-60x=147 | | 25z+5-8=147 | | 0.4-1.2=0.3r+0.6 | | 8q=32 | | 7(-2x+10)=42 | | 8(2-5x)=-264 | | 11.3+-7.2=3.82 | | 747-60x=0 | | 4y+5(5+y)=-2 | | ax+by=0 | | 2(-4r+2)=-6(-8+2r) | | .53y+2.5=5.1 | | -88+9z=z | | 3xz+4-8=1 | | 2(4d+5h)-(9h-5d)= | | 2x+1+4x+4=4 | | 7u-22=-1 | | -8(6x+5)=-520 | | 4h+7=4h | | x+3=30 | | 220+0.15x=368.50 | | (3x^2y+7xy^2)(x^2y^3-2y^2)= | | 11=1+8m+2n | | -5x-10=2-(x-4) | | 3(2+e)-4e=e+16 | | 9.1x+23.1=-4.2 | | (5x^5y^4)(2x^5y)= | | 21b=-19 |

Equations solver categories